O kwestii niezależności i transparentności w zawodzie biegłego rewidenta - Karpińska, Marzena (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The content analysis proves that in the case of statutory auditors, full and indubitable financial statement does not only constitute individual issue of attitudes presented by this professional group. The most important is the fact that stakeholders, as a basic institution which has influence on broader public interest, receive reliable information about financial situation of the business entity. It should be highlighted that focusing on public interest by statutory auditors is reflected in their independence and constitutes an important point of business ethics, which in turn makes it possible to determine clear limits of operation in markets in the globalizing world considering the ethics and a moral point of view.
Keywords: auditors; financial audit